Comparison Of Price Earning Ratio (PER) Textile Subsector Companies On Bei Before And After The Covid-19 Pandemic Period 2018-2022 - Ririn Jantri Welia; Seflidiana Roza; Nurhayati (LPPM STIE EKA PRASETYA, 2024)
This research aims to determine the difference in Price Earning Ratio (PER) before and after the Covid 19 pandemic in textile subsector companies listed on the Indonesian Stock Exchange (BEI) in 2018 - 2022. The samples used in this research were 14 samples from a population of 23 companies. Textile subsector listed on the IDX in 2018-2022. The method used in this research is the purposive sampling method. Based on the results of statistical tests, it can be concluded that there is no significant difference between the Price Earning Ratio before and the Price Earning Ratio after the Covid 19 Pandemic in Textile Subsector Companies, which is marked by │tcount│ < │ttable│. The significance value is 0.321. Based on the results of the significance test, it shows that the tcount value is -1.011. Tcount =│ -1.011│ < ttable = │2.052│ explained that H0 is accepted because tcount < ttable, then H1 is rejected. The sig value is more than the specified significance level. From an industrial perspective, it can be said that the Covid 19 pandemic has had no impact on share prices and earnings per share in the textile industry.